2002
DOI: 10.1128/aem.68.1.326-334.2002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Resource Factors Influencing High Microbial Diversity in Soil

Abstract: To begin defining the key determinants that drive microbial community structure in soil, we examined 29 soil samples from four geographically distinct locations taken from the surface, vadose zone, and saturated subsurface using a small-subunit rRNA-based cloning approach. While microbial communities in low-carbon, saturated, subsurface soils showed dominance, microbial communities in low-carbon surface soils showed remarkably uniform distributions, and all species were equally abundant. Two diversity indices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
370
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 598 publications
(426 citation statements)
references
References 36 publications
36
370
0
6
Order By: Relevance
“…Over a wide range of depths from tens of centimeters to meters, other researchers have shown that genetic diversity tends to decrease with increasing soil depth [18,24,34,35,61,75]. This decrease in diversity has been attributed to a variety of factors, including soil moisture and carbon and nitrogen availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over a wide range of depths from tens of centimeters to meters, other researchers have shown that genetic diversity tends to decrease with increasing soil depth [18,24,34,35,61,75]. This decrease in diversity has been attributed to a variety of factors, including soil moisture and carbon and nitrogen availability.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the spatially structured habitat, patchiness in nutrient availability, differences among associated plant species, or interactions among members of the soil community may all contribute to this diversity [10,14,22,31,51,60,65,70,75]. To identify local factors that may influence the spatial distribution of diversity, including competitive interactions and resource availability, information on how phenotypes and genotypes are arrayed in space is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Library coverage was calculated with the nonparametric estimator C (Good, 1953). The reciprocal of Simpson's index (1/D) was used as a measure of diversity to evaluate the level of dominance in a community (Zhou et al, 2002). The number of shared OTUs between libraries was calculated using SONS (www.mothur.…”
Section: Sequence Analysismentioning
confidence: 99%
“…chromium and many heavy metals, and recalcitrant organic contaminants. Zhou et al (2002) studied the microbial communities in different types of contaminated and pristine soils and aquifers, and found that even extremely high levels of Cr-III did not significantly influence microbial diversity. Similarly, at another site with aerobic groundwater contaminated by trichlorethylene (TCE) at low concentrations (0-3 ppm), no effect on the microbial community structure was observed.…”
Section: Impact Of Contaminations On Biocenoses In Pristine Aquifersmentioning
confidence: 99%